Pengaruh LMS Schoology terhadap Peningkatan Hasil Belajar Peserta Diklat PKP Angkatan VI BDK Surabaya - Wida Wido Yanto (Balai Diklat Keagamaan Semarang, 2020)
This research was based on the teaching and learning process now in the world of education which most of it still tends to be done conventionally. In the future, information and communication technology has an important role in learning, namely as learning content or learning media. The purpose of this study is to describe the ifluence of LMS Schoology on improving the learning outcomes of Training participants at the Supervisor Vocational Development Material PKP V Surabaya Religious Training Center 2020. Problem formulation: Is there any significant and positive influence on the use of LMS Schoology on Improving the learning outcomes of Training participants at the Supervisor Vocational Development Material? This research was conducted using a pre-experimental one group pretest-postets research method with regression analysis. Regression analysis was used to find out how much influence the independent variable had on the increase in the dependent variable. The results showed that after the teaching and learning process carried out with the LMS Schoology application the learning outcomes of the training participants increased. Empirical test results indicated the magnitude of the percentage of influence of the independent variables on the dependent variable of 77.4%. T test results showed the t value of 11.333 and p-value (Sig) of 0.000 which is below alpha 5%. was rejected, meaning that there was a significant and positive influence between LMS Schoology on improving the learning outcomes of training participants.